Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Nghị quyết Kỳ họp thứ 5, Quốc hội khóa XV - Uỷ ban Thường vụ Quốc hội (2023)
Toàn văn Báo cáo giải trình, tiếp thu, chỉnh lý dự thảo Nghị quyết Kỳ họp thứ 5, Quốc hội khóa XV.